FACTORS OF CUSTOMER SATISFACTION WITH THE QUALITY OF BANKING SERVICES AND PREDICTION OF THEIR SIGNIFICANCE - Mitić, Nina; Brzaković, Miodrag (Journal of process management and new technologies, 2023)
In modern business, the quality of products and services is, not without reason, given considerable attention. That is why it is understandable that quality is considered a key business paradigm in banking as well. In particular, the quality of banking services is viewed as an essential prerequisite for gaining new clients and retaining existing ones. In this paper, scientific attention is focused on researching the factors of customer satisfaction with the quality of banking services and predicting their importance. In line with that, a descriptive "survey" method (survey-research method) was applied, while other methods were not completely ignored, because without of them a complete answer to all the questions could not be given. By applying factor analysis (orthogonal varimax method), five factors were obtained, which were, in further data processing and analyzing the research results, treated as the main factors of client satisfaction with the quality of banking services. One-factor analysis of variance - ANOVA - was used to predict the importance of selected factors from the client’s point of view. The results of this research can contribute to the improvement of customer relations by improving the existing practice of managing customer relations.